THE VALUE OF SUBAHNALE IDENTITY IN THE DIGITAL DESIGN MATARAM CITY REGIONAL ELECTION MASCOT - Hasbullah, Hasbullah; Swandi, I Wayan; Udayana, Anak Agung Gde Bagus; Dewi, Alit Kumala (UPT Pusat Penerbitan LP2MPP ISI Bali, 2024)
Subahnale’s existence is not only in digital mascot designs but is widely used by the younger generation in illustration designs and others. However, what values are contained in Subahnale’s motives in communicating in the Mataram city elections? This research aims to examine the value of Subahnale’s identity in the digital design of the Mataram City Pilkada mascot. Using qualitative methods, data collection was carried out through interviews, visual analysis of Subahnale motifs, and literature reviews and was based on Roland Barthes' semiotic theory. The research results show that Subahnale’s mascot design will increase its aesthetic appeal. Subahnale is digitally relevant in modern visual communication, demonstrating emotional value that encourages community involvement and strengthens local identity. The implications of the results of this research strengthen the political value of branding in safe, honest, and fair regional election activities.